The Effectiveness of Somatic, Auditory, Visualization, and Intellectually and Numbered Head Together Learning Models Against Students' Mathematical Problem Solving Capabilities - Purnama, Syahfitri; Siswadi, Siswadi; Pitaloka, Anggun; Maharani, Intan Putri (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aims to examine the effectiveness of the Somatic, Auditory, Visualization and Intellectualy (SAVI) and Numbered Head Together (NHT) learning models on students' mathematical problem solving abilities. This research is included in the type of quantitative research. The research sampling technique uses the random sample method. Using the T-Test as a data processing analysis technique with a significance level α = 0,05. Obtained research results indicate that there are very significant differences in students' mathematical problem solving abilities. Students who use the NHT learning model have problem-solving abilities that are superior to students who use the SAVI learning model. This is evident from the mean value of descriptive data that is 80.88 for the NHT learning model and the SAVI learning model obtained a mean value of 68.24, in addition from the T test also concluded that there are significant values for both models.